Atomically Precise Ruddlesden-Popper Faults Induced Enhanced Emission in Ligand Stabilized Mixed Halide Perovskites - Mahato, Somnath (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.